A preliminary look at personality analysis as a coaching strategy / Wee Eng Hoe and Tan Chee Hian - Wee, Eng Hoe; Tan, Chee Hian (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2012)
This paper explores the need to understand athletes' personalities in ensuring favourable coaching outcomes. Successful coaching cannot be judged based solely on winning or losing but also based on the development of athletes. As such, the process of coaching must be changed to involve the learning of athletes' personality types. No two athletes are the same but many have similar characteristics. The understanding of personality would enable coaches to cater their approaches to athletes accordingly and achieve positive outcomes without enduring unnecessary stress. Although some researchers have found contradictions and difficulties in personality research based on sports due to the different methodologies used, this paper will embark on two approaches to explore the issue. The approaches are the review of literature on personality types and the presentation of the findings of local studies based on different personality models. Specifically, the review will include behaviour characteristics of athletes, personality traits of athletes from individual and team sports, athletes' personalities from different types of sports, personality and ability to learn motor skills, personality differences between contact and non-contact sports and personality differences with different body types. The local studies will focus on Sanguine-Choleric- Melancholic and Phlegmatic Model (SCMP) and The Big-Five Model. Based on the findings, strategies will be suggested for coaches to address the difficulties faced in coaching athletes with diverse personality.